Origins of Very-Low and Zero-Energy Electron Structures in Strong-Field Ionization with Intense Mid-IR Pulses. (August 2015) - Wolter, B; Lemell, C; Baudisch, M; Pullen, M G; Tong, X-M; Hemmer, M; Senftleben, A; Sclafani, M; Schröter, C D; Ullrich, J; Moshammer, R; Burgdörfer, J; et al.
Synopsis: Intense long wavelength (λ ≥ 2 μm) laser pulses enable experiments in the tunneling ionization regime (γ ≪ 1) and reveal surprising low electron energy features, which can not be described with the strong-field approximation (SFA). These features, universal for all target species, include the low-energy structure (LES), the very-low-energy structure (VLES) and the zero-energy structure (ZES). Using full 3D electron-ion coincidence detection in combination with our ultrafast 160 kHz mid-IR source, we reveal the entire 3D momentum spectrum well below 1 eV. Quantum and classical simulations allow for an interpretation of the LES, VLES and of the newly identified ZES.